SodhanaRef: a reference management software built using hybrid semantic measure - Kiran, Mandava Kranthi; Reddy, K Thammi (International Journal of Engineering and Technology, 2018)
Reference management softwares are widely used by the researchers to maintain their collection of scholarly literature that exist in PDF format. Though widely used most of the reference management softwares have no sophisticated Information retrieval except few which offer advanced search that includes search for title, author etc., These softwares in the present day market do not give importance to the semantic similarity or relatedness concept, query expansion and finding the context within the query to find the concept behind the user mentioned query.With SodhanaRef, a solution is offered to deal with the above-mentioned issues by building reference management software using a mix up of corpus-based and knowledge-based semantic measures. Based on the evolution done on about 200 various scholarly literatures in the PDF form, SodhanaRef shows a good performance over Mendeley when compared between these two reference management softwares for title search. The other evaluations for finding the semantic similarity between the user mentioned query and the existing titles in the title search and for identifying the concept behind the query along with identifying the concept of a research publication have shown good results with an average precision between 0.8 to 1 for each query.